A Study On Leachate Cod Fractions From Semi-Aerobic Landfill - Adam, Nor Hana (2011)
The purpose of this research is to characterize leachate from Pulau Burung sanitary landfill (PBSL). PBSL is a semi-aerobic landfill which applies Fukuoka Method to reduce the amount of methane and enhance the stability of landfill compared to anaerobic types. This study compares two types of leachate, namely young and old. The study was carried out to determine the suitable method to determine the fractions of COD which has significant value as a contaminant parameter. The COD fractions include slowly biodegradable COD (Sbsi), readily biodegradable COD (Sbsi), soluble unbiodegradable COD (Susi) and particulate unbiodegradable COD (Supi).